PENGGUNAAN PRINSIP SYARIAH DALAM BERBISNIS PADA PENGUSAHA - Laksono, Dizza Ludfi; Muttaqin, Aminnullah Achmad (Journal of Development Economic and Social Studies, 2024)
Business activities with sharia principles in this journal are seen from researcher observations and start from things that are clearly visible. Researchers want to know the motives behind changes in behavior, business operating procedures, and feedback on entrepreneurs who apply sharia principles to their business. The research was conducted in Sidoarjo Regency and aimed to find out the underlying reasons for entrepreneurs conducting business using sharia principles. The methodology used in this research is qualitative with a phenomenological approach. Data collection technique strategy was dept-interview with semi-structured methods, researchers managed to find 11 informants. The results of this research are entrepreneurs who intend to apply sharia principles which are not far from the explanations of the Qur'an and hadith and imitate the behavior of the prophet Muhammad ﷺ in doing business with the aim of complying with Islamic rules and prohibitions. For instance, not allowed to serve costumer during salah occurred, for entrepreneurs engaged in product, must not reduce scale in transaction, keep a promised negotiation, and for entrepreneur in services sales, that have to nurture as best as they can without belittling others. Other results stated that after implementing sharia principles, employees were able to work sincerely and customers almost never felt disappointed.